Socio-economic context of begging among elderly in Nigeria (2014)
This study utilised a context-based analysis of field observations and fifteen in-depth interviews to examine how begging is practiced by the elderly in a city in Southwestern Nigeria. As both sub-categories of beggars in the population and the larger elderly persons in the society, elderly beggars are a distinct demographic group whose needs differ from the rest of the population. Adopting a livelihood perspective as the exploratory frame, the study explains how beggary constitutes a rational response to economic, social, physiological, institutional and structural imperatives, adopted b) old people as a strategy for improving their wellbeing. The study concluded that in trying to eradicate begging among elderly, the context of their emergence must be duly examined and given considerable attention in the policy process. Efforts should also be directed at supporting households headed by the elderly as means of removing the most fundamental social and economic situations that promote begging among oh people.